Counter-narratives of religious radicalism through mosque-based Islamic education to build inclusive religiosity in Indonesia - Marzuki Marzuki; Benni Setiawan; Sun Choirol Ummah (Universitas Negeri Yogyakarta, 2023)
This research is motivated by the emergence of various acts of violence in the name of religion, especially Islam, which have disturbed society and the state. One form of acts of violence is based on narrow religious thoughts which ultimately lead to radical actions. This research aims to counter-narrate religious radicalism through mosque-based Islamic education as joint efforts to build inclusive religiosity in Indonesia. This study is a qualitative research in the form of case stury. The location of this study is Batam City, Riau Islands. Data collection uses observation, interviews, and focus group discussion (FGD) techniques and is assisted with documentation. Data analysis uses interactive analysis techniques. The results of the research found a formulation of mosque-based Islamic education in Batam City which was attempted by Islamic leaders and figures who are members of an organization called the Persatuan Muballigh Batam (Batam Muballigh Association), Nahdlatul Ulama, and Muhammadiyah. It is through Islamic education that religious (Islamic) activities in Batam City have been successfully controlled, especially through maximizing the role of the mosque as the center of Islamic education so as to ensure the implementation of moderate and tolerant Islamic teachings. This research also found a counter-narrative formulation of religious radicalism in order to build a civilized and inclusive Muslim society in Indonesia.